A new species of Alvinocaris (Crustacea: Decapoda: Caridea: Alvinocarididae) from Costa Rican methane seeps - Martin, Joel W.; Wall, Adam R.; Shank, Tim; Cha, Harim; Seid, Charlotte A.; Rouse, Greg W. (Zootaxa, 2018)
A new caridean shrimp, Alvinocaris costaricensis, is described from methane seeps in the eastern Pacific off Costa Rica. The new species is the 16th described species of the genus, and by molecular analysis appears closest to Alvinocaris komaii from the Lau Basin, southwestern Pacific, but shares certain morphological characters with A. lusca from the Galapagos Rift and A. muricola from the West Florida Escarpment, as well as with A. kexueae from the Manus Basin in the Southwest Pacific.